Polymer type catalyst as well as preparation method and application thereof

By using polymer catalysts in electrocatalytic nitric acid reduction reaction, the environmental and economic problems of the hydroxylamine production method in the prior art are solved, and efficient, environmentally friendly and low-cost hydroxylamine preparation is achieved, and the catalyst is non-toxic and highly active.

CN119710787AActive Publication Date: 2025-03-28UNIV OF SCI & TECH OF CHINA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411916088.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-28
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing hydroxylamine production methods have problems such as unfriendly environment, high cost, low yield, high low-priced by-products, and serious carbon emissions. The existing catalysts are toxic, low-activity, and unselectivity.

Method used

Hydroxylamine is prepared in electrocatalytic nitric acid reduction reaction using polymer catalyst. The polymer catalyst is made of carbon fiber paper with a porous structure as the substrate, and conductive polymers (such as polypyrrole) are formed on the substrate surface and are prepared by in-situ electropolymerization reaction.

Benefits of technology

It achieves a high Faraday efficiency and yield, while the catalyst is non-toxic, has high activity and stability, and is suitable for green, low-cost, low-carbon and sustainable hydroxylamine preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005206941620000011
    Figure HDA0005206941620000011
  • Figure HDA0005206941620000012
    Figure HDA0005206941620000012
  • Figure HDA0005206941620000013
    Figure HDA0005206941620000013
Patent Text Reader

Abstract

The invention provides application of a polymer type catalyst in preparation of hydroxylamine through an electro-catalysis nitric acid reduction reaction. The polymer type catalyst is composed of a substrate and a conductive polymer formed on the surface of the substrate, and the substrate is carbon fiber paper with a porous structure. The invention also provides a polymer type catalyst and a preparation method thereof. The carbon fiber paper is used as a substrate, the polymer type catalyst coating the surface of the carbon fiber paper is obtained through an in-situ electrodeposition reaction, the catalyst is used for preparing hydroxylamine through electro-catalysis nitric acid reduction, and high Faraday efficiency and yield are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and in particular to a polymer catalyst, a preparation method thereof and application thereof. Background Art

[0002] In the production and life of human society, hydroxylamine, as an important chemical intermediate, is widely used in fine chemical fields such as medicine, pesticides, textiles, and electronics. With the continuous improvement of the penetration rate of hydroxylamine in the fine chemical market, the demand for hydroxylamine in the Chinese market has increased year by year. Based on this, the development of efficient preparation technology of hydroxylamine is of great significance to improve the deep utilization of nitrogen.

[0003] At present, the existing production methods of hydroxylamine face challenges such as environmental unfriendliness, high cost, low yield, many low-cost by-products, and serious carbon emissions. It is urgent to develop a new green, low-cost, low-carbon and sustainable process for the preparation of hydroxylamine. 3- The technology of electrosynthesizing hydroxylamine as a nitrogen source has significant advantages. However, existing catalysts have problems such as certain toxicity, low activity, and low selectivity. There is an urgent need to develop a non-toxic catalyst that has both high selectivity and high activity. Summary of the invention

[0004] The technical problem solved by the present invention is to provide an application of a polymer catalyst in the preparation of hydroxylamine by electrocatalytic nitric acid reduction reaction. The application of the polymer catalyst in the preparation of hydroxylamine can achieve higher Faradaic efficiency and yield.

[0005] In view of this, the present application provides an application of a polymer catalyst in the preparation of hydroxylamine by electrocatalytic nitric acid reduction reaction;

[0006] The polymer catalyst consists of a substrate and a conductive polymer formed on the surface of the substrate, and the substrate is carbon fiber paper with a porous structure.

[0007] Preferably, the electrocatalytic nitric acid reduction reaction is specifically:

[0008] A bipolar membrane was used as the ion exchange membrane, a polymer catalyst, a platinum wire, and silver / silver chloride were used as the working electrode, the counter electrode, and the reference electrode, respectively, an aqueous nitric acid solution was used as the cathode electrolyte, and an aqueous sulfuric acid solution was used as the anode electrolyte, and the reaction was carried out under a nitrogen atmosphere.

[0009] Preferably, the flow rate of the nitrogen gas is 10 to 30 mL / min, the concentration of the aqueous nitric acid solution is 0.5 to 2 mol / L, and the concentration of the aqueous sulfuric acid solution is 0.1 to 1.5 mol / L.

[0010] The present application also provides a polymer catalyst, which is composed of a substrate and a conductive polymer;

[0011] The conductive polymer is formed on the surface of the substrate, and the substrate is a carbon fiber with a porous structure.

[0012] Preferably, the conductive polymer is polypyrrole.

[0013] The present application also provides a method for preparing the polymer catalyst, comprising the following steps:

[0014] Mixing a conductive polymer monomer, an oxidant and deionized water to obtain an electrodeposition solution;

[0015] Carbon fiber paper with a porous structure is used as a working electrode and a counter electrode respectively, and silver / silver chloride is used as a reference electrode. The working electrode, the counter electrode and the reference electrode are placed in the electrodeposition solution to carry out an in-situ electropolymerization reaction to obtain a polymer catalyst.

[0016] Preferably, the conductive polymer monomer is pyrrole, the oxidant is lithium perchlorate trihydrate, and the ratio of the deionized water, the pyrrole and the lithium perchlorate trihydrate is (50-100) mL: (400-500) μL: (1.0-1.5) g.

[0017] Preferably, the current of the in-situ electropolymerization reaction is 10 to 30 mA, and the time is 30 to 90 seconds.

[0018] Preferably, the in-situ electropolymerization reaction further comprises:

[0019] The working electrode is turned over and a current of 10 to 30 mA is applied again for 30 to 90 seconds.

[0020] Preferably, the coulomb amount required for depositing the conductive polymer per square centimeter of the carbon fiber paper surface is 1-3C.

[0021] The present application provides the use of a polymer catalyst in the preparation of hydroxylamine by an electrocatalytic nitric acid reduction reaction, wherein the polymer catalyst is composed of a substrate and a conductive polymer formed on the surface of the substrate, and the substrate is a carbon fiber paper with a porous structure; since the polymer catalyst has the characteristics of being recyclable and having high stability, the polymer catalyst is used in the electrocatalytic nitric acid reduction reaction to prepare hydroxylamine, which can achieve a higher Faraday effect and yield. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the polymer catalyst prepared in Example 1 of the present invention;

[0023] Figure 2 This is the Raman spectrum of the polymer catalyst prepared in Example 1 of the present invention;

[0024] Figure 3 This is a Faraday efficiency diagram of the polymer catalyst prepared in Example 1 of the present invention for generating hydroxylamine at different set potentials;

[0025] Figure 4 is a partial current density variation trend diagram of the polymer catalyst prepared in Example 1 of the present invention for generating hydroxylamine at different set potentials;

[0026] Figure 5 This is a catalyst stability diagram of the polymer catalyst prepared in Example 1 of the present invention tested at a potential of -2.01V for 250h. DETAILED DESCRIPTION

[0027] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0028] In view of the fact that catalysts for synthesizing hydroxylamine in the prior art have problems such as toxicity, low activity, and low selectivity, the present application provides the use of a polymer catalyst in the preparation of hydroxylamine by electrocatalytic nitric acid reduction reaction, which can achieve a high Faraday effect and yield while being non-toxic. Specifically, an embodiment of the present invention discloses the use of a polymer catalyst in the preparation of hydroxylamine by electrocatalytic nitric acid reduction reaction;

[0029] The polymer catalyst consists of a substrate and a conductive polymer formed on the surface of the substrate, and the substrate is carbon fiber paper with a porous structure.

[0030] In the present application, the electrocatalytic nitric acid reduction reaction is specifically:

[0031] A bipolar membrane was used as the ion exchange membrane, a polymer catalyst, a platinum wire, and silver / silver chloride were used as the working electrode, the counter electrode, and the reference electrode, respectively, an aqueous nitric acid solution was used as the cathode electrolyte, and an aqueous sulfuric acid solution was used as the anode electrolyte, and the reaction was carried out under a nitrogen atmosphere.

[0032] In the above electrocatalytic nitric acid reduction reaction, the bipolar membrane, the platinum wire, and the silver / silver chloride are all materials well known to those skilled in the art, and this application does not impose any special restrictions on this. The concentration of the nitric acid aqueous solution is 0.5-2 mol / L, specifically, the concentration of the nitric acid aqueous solution is 1-1.5 mol / L; the concentration of the sulfuric acid aqueous solution is 0.1-1.5 mol / L, specifically, the concentration of the sulfuric acid aqueous solution is 0.5-1 mol / L. ; The nitrogen is used as a protective gas and a carrier gas, and its purity is 99.999%; the flow rate of the nitrogen is 10-30 mL / min, specifically, the flow rate of the nitrogen is 10-20 mL / min.

[0033] In the process of preparing hydroxylamine by electrocatalytic nitric acid reduction reaction, the polymer catalyst is used as a catalyst, which is non-toxic and has high activity.

[0034] Furthermore, the present application also provides a polymer catalyst, which is composed of a substrate and a conductive polymer;

[0035] The conductive polymer is formed on the surface of the substrate, and the substrate is carbon fiber paper with a porous structure.

[0036] In the polymer catalyst of the present application, the conductive polymer is polypyrrole; the polypyrrole is coated on the surface of the substrate. The substrate is specifically selected from carbon fiber paper with a porous structure, which has the characteristics of conductivity, air permeability, corrosion resistance, etc.; the source of the carbon fiber paper is not particularly limited in the present application and can be a commercially available product.

[0037] In the present application, the polypyrrole in the polymer catalyst serves as the main catalytic component in the electrocatalytic nitric acid reduction reaction and provides catalytic reaction sites. The carbon fiber paper serves as the catalyst substrate and the main conductive medium in the electrocatalytic nitric acid reduction reaction. The above structure provides a large number of catalytic reaction sites in the electrocatalytic nitric acid reduction reaction, has good conductivity and is stable during the reaction.

[0038] The present application also provides a method for preparing a polymer catalyst, comprising the following steps:

[0039] Mixing a conductive polymer monomer, an oxidant and deionized water to obtain an electrodeposition solution;

[0040] Carbon fiber paper with a porous structure is used as a working electrode and a counter electrode respectively, and silver / silver chloride is used as a reference electrode. The working electrode, the counter electrode and the reference electrode are placed in the electrodeposition solution to carry out an in-situ electropolymerization reaction to obtain a polymer catalyst.

[0041] In the preparation process of the polymer catalyst, the present application first mixes a conductive polymer monomer, an oxidant and deionized water to obtain an electrodeposition solution. In the present application, the conductive polymer monomer is selected from pyrrole, and the oxidant is selected from lithium perchlorate trihydrate; the ratio of the deionized water, the pyrrole and the lithium perchlorate trihydrate is (50-100) mL: (400-500) μL: (1.0-1.5) g; specifically, the ratio of the deionized water, the pyrrole and the lithium perchlorate trihydrate is (60-90) mL: (450-490) μL: (1.1-1.3) g; more specifically, the ratio of the deionized water, the pyrrole and the lithium perchlorate trihydrate is 70 mL: 485 μL: 1.1231 g; at this ratio, the molar ratio of pyrrole to lithium perchlorate is about 1:1, and pyrrole can be fully in-situ electropolymerized to ensure the in-situ generation of polypyrrole.

[0042] The present application then in situ deposits polypyrrole on the surface of the carbon fiber paper by an in situ electrodeposition reaction, that is, the carbon fiber paper with a porous structure is used as the working electrode and the counter electrode respectively, and silver / silver chloride is used as the reference electrode, and the working electrode, the counter electrode and the reference electrode are placed in the electrodeposition solution for in situ electropolymerization reaction to obtain a polymer catalyst; in the above step of obtaining the polymer catalyst, the areas of the carbon fiber paper of the working electrode and the counter electrode are equal, and the two are placed in parallel with a spacing of 0.8 to 1.5 cm, and the areas of the carbon fiber paper are both 0.8 to 2 cm 2 Specifically, the distance between the working electrode and the counter electrode is 1 cm, and the area is 1 cm 2 ; The in-situ electropolymerization reaction is carried out at room temperature of 20 to 30°C without stirring. The current of the in-situ electropolymerization reaction is 10 to 30 mA, and the time is 30 to 90 s; specifically, the current of the in-situ electropolymerization reaction is 20 to 25 mA, and the time is 40 to 60 s. Furthermore, after the above-mentioned in-situ electropolymerization reaction, it also includes: turning the working electrode so that its back is facing the counter electrode, and applying a current of 10 to 30 mA again for 30 to 90 s; specifically, the current is 20 to 30 mA for 40 to 60 s. In the polymer catalyst, the coulomb amount required to deposit polypyrrole on each square centimeter of carbon fiber paper is 1 to 3C, more specifically 2.4C. Compared with the traditional method of preparing polymer catalysts, in-situ electropolymerization is simpler and more environmentally friendly, and can form a better electrode microstructure, providing more reaction sites for electrocatalytic reactions.

[0043] The preparation method of the polymer catalyst provided in the present application is simple, easy to synthesize in large quantities and has low cost.

[0044] In the method for obtaining hydroxylamine by electrocatalytic nitric acid reduction of the present invention, a polymer catalyst is introduced and the polymer catalyst is directly used as a working electrode, thereby successfully realizing the electrocatalytic nitric acid reduction reaction to prepare hydroxylamine with high Faraday efficiency and yield.

[0045] In order to further understand the present invention, the polymer catalyst provided by the present invention, its preparation method and application are described in detail below in conjunction with the examples. The protection scope of the present invention is not limited by the following examples.

[0046] The raw materials in the following examples are all commercially available products, among which the carbon fiber is TGP-H-060 produced by Toray Industries, Japan.

[0047] Example 1 Preparation of polymer catalyst

[0048] 1.1231 g of LiClO4·3H2O was dissolved in 70 mL of deionized water, and 485 μL of pyrrole was added, and the mixture was ultrasonically stirred. After the pyrrole was completely dissolved, an electrodeposition solution of a polymer catalyst was obtained. Carbon fiber paper was used as a working electrode and a counter electrode, and a silver / silver chloride electrode was used as a reference electrode. The electrodes were placed in the electrodeposition solution of the catalyst for in-situ electropolymerization reaction, and a current of 20 mA was applied for 60 seconds, and the electrode was taken out for rinsing. The working electrode was then turned over so that its original back side was facing the counter electrode, and an oxidation current of 20 mA was applied again for 60 seconds. The electrode was taken out and washed with deionized water. A polymer catalyst with polypyrrole coated on the surface of the carbon fiber paper was obtained.

[0049] The polymer catalyst obtained in Example 1 was analyzed using a scanning electron microscope and a laser Raman spectrometer. Figure 1 As shown, Figure 1 This is a scanning electron microscope image of the polymer catalyst prepared in this example. Figure 1 It can be seen that the polymer of the polymer catalyst is evenly coated on the surface of the carbon fiber, showing a wrinkled morphology; the Raman spectrum is shown in Figure 2 As shown, Figure 2 This is the Raman spectrum of the polymer catalyst prepared in this example, which confirms that the synthesized polymer catalyst is polypyrrole.

[0050] Example 2 Product selectivity test of polymer catalyst in electrocatalytic nitric acid reduction

[0051] In an H-type electrolytic cell, a bipolar membrane is used as an ion exchange membrane, the polymer catalyst obtained in Example 1 is used as a working electrode, a platinum wire is used as a working electrode, a silver / silver chloride reference electrode is used, a 1 mol / L nitric acid aqueous solution is used as a cathode electrolyte, a 0.5 mol / L sulfuric acid aqueous solution is used as an anolyte, a magnetic stirrer is used to control the rotor speed in the cathode liquid to be 500 rpm, and nitrogen with a purity of 99.999% is used as a protective gas and a carrier gas, and the gas flow rate is 20 mL / min;

[0052] Under the following reaction conditions, a constant potential test was conducted: the potential was set to -2.21V (relative to the standard hydrogen electrode), the constant potential test lasted for 3600s, during the reaction, nitrogen was used as the carrier gas, and the nitrogen flow rate was set to 20mL / min; the gaseous product was blown out and blown into the gas chromatograph for online detection of hydrogen, the chromatographic tail gas was collected with an air bag, and the gaseous nitrogen oxide content was detected using an infrared gas detector, and the oxygen produced at the anode during the reaction was discharged into the air; after the reaction was completed, an excess of glyoxylic acid was added to the cathode liquid, and the liquid product was detected by nuclear magnetic resonance hydrogen spectroscopy. After the test was completed, the total potential was set to -2.01V, -1.81V, -1.61V, and -1.41V (all relative to the standard hydrogen electrode), and other conditions were kept unchanged for testing, and the Faraday efficiency of the polymer catalyst for electrocatalytic reduction of nitric acid to prepare hydroxylamine was obtained. Figure 3 , the partial current density of hydroxylamine is Figure 4 ; Figure 3 is a Faraday efficiency diagram of the polymer catalyst prepared in Example 1 of the present invention for generating hydroxylamine at different set potentials, Figure 3 It can be seen that in the potential range of -1.41 to -2.21 V relative to the standard hydrogen electrode, the Faraday efficiency of the polymer catalyst for hydroxylamine is greater than 70.0%. When the potential is -2.21 V, the Faraday efficiency of hydroxylamine is the highest, which is 78.9%. This shows that the polymer catalyst prepared in the present application has a high selectivity in the preparation of hydroxylamine. Figure 4 is a partial current density variation trend diagram of the polymer catalyst prepared in Example 1 of the present invention to generate hydroxylamine at different set potentials, Figure 4 It can be seen that in the potential range of -1.41 to -2.21 V relative to the standard hydrogen electrode, the partial current density of hydroxylamine increases as the potential becomes negative. When the potential is -2.21 V, the partial current density of hydroxylamine is the largest, which is -368.0 mA cm -2 ; This shows that the polymer catalyst prepared in the present application has high activity in the preparation of hydroxylamine.

[0053] Example 3 Stability test of polymer catalyst in electrocatalytic nitric acid reduction

[0054] Under the reaction conditions of Example 2, a constant potential test was performed: the potential was set to -2.01 V (relative to the standard hydrogen electrode), the constant potential test was performed for 36,000 seconds, and nitrogen was used as a protective gas during the reaction. The tail gas was discharged into the air, and the oxygen produced by the anode during the reaction was discharged into the air. After the reaction was completed, an excess of glyoxylic acid was added to the cathode liquid, and the liquid product was detected by nuclear magnetic resonance amine spectroscopy. This is one round of testing. After the completion of this round of testing, the cathode liquid was replaced with fresh, unreacted cathode liquids, and other conditions remained unchanged for testing, and this cycle was repeated until the catalyst performance showed a significant decrease, and finally the stability data of the polymer catalyst for electrocatalytic nitric acid reduction to prepare hydroxylamine was obtained.

[0055] Figure 5 The stability diagram of the polymer catalyst prepared in Example 1 of the present invention to generate hydroxylamine at a potential of -2.01 V relative to the standard hydrogen electrode; Figure 5 It can be seen that a total of 25 rounds of tests were carried out, totaling 250 hours, that is, the polymer catalyst can stably electrocatalyze nitric acid reduction for 250 hours, during which the Faradaic efficiency of hydroxylamine remained above 60%, and the maximum concentration remained above 260 mmol.

[0056] The above embodiments are only used to help understand the method and core idea of ​​the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

[0057] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. Application of a polymer catalyst in the preparation of hydroxylamine by electrocatalytic nitric acid reduction reaction; The polymer catalyst consists of a substrate and a conductive polymer formed on the surface of the substrate, and the substrate is carbon fiber paper with a porous structure.

2. The use according to claim 1, characterized in that: The electrocatalytic nitric acid reduction reaction is specifically: A bipolar membrane was used as the ion exchange membrane, a polymer catalyst, a platinum wire, and silver / silver chloride were used as the working electrode, the counter electrode, and the reference electrode, respectively, an aqueous nitric acid solution was used as the cathode electrolyte, and an aqueous sulfuric acid solution was used as the anode electrolyte, and the reaction was carried out under a nitrogen atmosphere.

3. The use according to claim 2, characterized in that: The flow rate of the nitrogen gas is 10-30 mL / min, the concentration of the nitric acid aqueous solution is 0.5-2 mol / L, and the concentration of the sulfuric acid aqueous solution is 0.1-1.5 mol / L.

4. A polymer catalyst, consisting of a substrate and a conductive polymer; The conductive polymer is formed on the surface of the substrate, and the substrate is a carbon fiber with a porous structure.

5. The polymer catalyst according to claim 1, characterized in that The conductive polymer is polypyrrole.

6. The method for preparing the polymer catalyst according to claim 4, comprising the following steps: Mixing a conductive polymer monomer, an oxidant and deionized water to obtain an electrodeposition solution; Carbon fiber paper with a porous structure is used as a working electrode and a counter electrode respectively, and silver / silver chloride is used as a reference electrode. The working electrode, the counter electrode and the reference electrode are placed in the electrodeposition solution to carry out an in-situ electropolymerization reaction to obtain a polymer catalyst.

7. The preparation method according to claim 6, characterized in that: The conductive polymer monomer is pyrrole, the oxidant is lithium perchlorate trihydrate, and the ratio of the deionized water, the pyrrole and the lithium perchlorate trihydrate is (50-100) mL: (400-500) μL: (1.0-1.5) g.

8. The preparation method according to claim 6, characterized in that: The current of the in-situ electropolymerization reaction is 10-30 mA, and the time is 30-90 seconds.

9. The preparation method according to claim 6, characterized in that: The in-situ electropolymerization reaction further comprises: The working electrode is turned over and a current of 10 to 30 mA is applied again for 30 to 90 seconds.

10. The preparation method according to claim 6, characterized in that: The coulomb amount required to deposit the conductive polymer per square centimeter of carbon fiber paper surface is 1 to 3C.

Citation Information

Patent Citations

  • Nitrate-containing catalyst for ammonia production through reduction as well as preparation method and application of nitrate-containing catalyst

    CN115976570A

  • Preparation method of copper-based catalytic material and electrode constructed based on hydrogel and application of copper-based catalytic material and electrode in ammonia production through nitrate reduction

    CN116254573A

  • Supported catalyst as well as preparation method and application thereof

    CN116426956A

  • Aromatic five-membered heterocyclic polymer composite material as well as preparation method and application thereof

    CN118347983A

  • Method for synthesizing hydroxylamine through ketoxime-mediated conductive catalysis

    CN118992980A